Combined effects of double rotating cones and magnetic field on the mixed convection of nanofluid in a porous 3D U-bend - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier Ltd, 2020)
Impacts of double rotating cone system and magnetic field on mixed convection in a 3D U-shaped porous channel are analyzed with finite element method. Impacts of different influencing parameters such as Richardson number (between 0.05 and 50), Hartmann number (between 0 and 100), rotational speed of the cones (between ?5000 and 5000), size of the cones (between 0 and 0.075H) and aspect ratio (between 0.4 and 2) on the flow and heat transfer are scrutinized. It was revealed that the average Nu decreases when higher values of Richardson number, magnetic field strength are considered while the impact is reverse for angular speed, size and aspect ratio of the cones. The hot walls of the U-channel contribute to overall heat transfer differently and the variation is significant for different pertinent parameters. The average Nu of hot wall near the exit is reduced by about 20% at the highest Richardson number. The magnetic field reduced the effective convention while significant increment of the average Nusselt number of the bottom wall is observed with higher size and speed of the rotating cones. The size effect is influential in the case of rotation and up to 143% increment in the average Nu is attained for the highest size with highest speed of the cones while this amount is only 9.5% for a stationary cone. Enhancements up to 84% in the average Nu is obtained with rotation of the cones while aspect ratio contributed to only 10% increment. A multi-parametric POD analysis for the evaluation of local and average Nusselt numbers of the hot surfaces of the U-shaped cavity is performed. The number of modes required to represent the data in the parametric space is 20, 20 and 48 for left, right and bottom surfaces. © 2020 Elsevier Ltd
Keywords: 3D cavity; Double cone; Finite element method; MHD flow; POD; Porous media; Rotating surface